Pengukuran Keimanan: Perspektif Psikologi - Shodiq, Shodiq (Nadwa, 2014)
Faith material is the basic and essential part of the learning goals in the con-text of strengthening the students personalities, especially in teaching reli-gious education. As the purpose of learning, faith must also be evaluated and measured so that it is known to what extent the learning objectives have been achieved. The problem is how to evaluate and measure ones faith? Only Allah can measure and determine the degree of ones faith, donât you? How to measure the faith will be discussed in this paper. This study would be useful for teachers in detecting an increase or decrease of the quality of students faith in accordance with the indicators that have been determined.